คำว่า "เป็น" ที่มีความหมายว่า "มีชีวิต" และ "รู้วิธี" : คำหลายความหมายหรือคำพ้องรูปพ้องเสียง? = The word /pen/ meaning ’to be alive’ and ’to know how to do’ in Thai : polysemy or homonymy? - Jaratjarungkiat, Sureenate (2021)
This article aimed at studying the word /pen/ meaning ‘to be alive’ and ‘to know how to do’ in Thai. The question addressed here was: should they be considered as polysemy or as homonymy? The collected data was based on written records from the Sukhothai period right up until the present. It was found that the word /pen/ meaning ‘to be alive’ and ‘to know how to do’ should be considered as polysemy. This is because, although these 2 meanings of /pen/ are quite different, the historical development shows that both meanings are related. That is to say, the word /pen/ meaning ‘to be alive’ is the original word and then develop into the word /pen/ meaning ‘to arise’ and then ‘to know how to do’, respectively. In addition, these changes emerge under 2 processes: metonymic process and metaphorical process. บทความนีÊมีวัตถ»ประสงค์ÁพืÉอศึกษาว่าคÎาว่าvÁปÈนwทีÉมีความหมายว่าtมีชีวิตuÁช่นป¼ต ́วน ̧Êย ́งÁปÈน°ย¼่ÂละคÎาว่าvÁปÈนwทีÉมีความหมายว่าtร¼้วิธีuÁช่นว่μยนÎÊμÁปÈนÁปÈนคÎาหลายความหมาย(polyseme)หรือÁปÈนÁพียงคÎาพ้องร¼ปพ้องÁสียง(homonym)Ãดยศึกษาจากข้อม¼ลภาษาทีÉตีพิมพ์ÂละÁผยÂพร่Âล้วตัÊงÂต่สมัยส»Ãขทัยจนถึงปัจจ»บันถึงÂม้ว่าคÎาว่าvÁปÈนwทีÉมีความหมายว่าtมีชีวิตuÂละtร¼้วิธีuจะมีความหมายทีÉÂตกต่างกันÂต่ผลการศึกษาพบว่าคÎาว่าvÁปÈนwทัÊง2ความหมายจัดÁปÈนคÎาหลายความหมายÁพราะการศึกษาข้อม¼ลÁชิงประวัติทÎาÄห้ทราบว่าความหมายทัÊง2มีความÁกีÉยวข้องกันกล่าวคือคÎาว่าvÁปÈนwทีÉมีความหมายว่าtมีชีวิตuÁปÈนความหมายทีÉÁกิดÁปÈนอันดับÂรกจากนัÊนกÈพัฒนาÅปÁปÈนความหมายว่าtบังÁกิดuÂละtร¼้วิธีuตามลÎาดับการÁปลีÉยนÂปลงข้างต้นผ่านกระบวนการทางความหมาย2กระบวนการÅด้Âก่กระบวนการนามนัยÂละกระบวนการอ»ปลักษณ์